EVALUATION OF SOME NOVEL INSECTICIDES AGAINST MYZUS PERSICAE (SULZER) - GAVKARE, OMKAR; KUMAR, SURJEET; SHARMA, NIKHIL; P. L SHARMA, (The Bioscan, 2013)
Realtive toxicity of some insecticides viz., acetamiprid, fipronil, imidacloprid, lambda cyhalothrin, malathion and thiamethoxam to apterous adults of the green peach aphid, Myzus persicae (Sulzer) was evaluated in the laboratory using leaf dip method of bioassay. The LC50 values of these insecticides were calculated to be 17, 16.5, 4.5, 15.4, 362.2 and 4.1 ppm, respectively. On the basis of LC50 values, thiamethoxam was found to be the most toxic insecticide with LC50 value of 4.1ppm, closely followed by imidacloprid with LC50 value as 4.5ppm. Malathion was found to be the least toxic with LC50 value of 362.2ppm.